PERANCANGAN APLIKASI GAME EDUKASI BERBASIS A UGMENTED REALITY (AR) PADA MATA PELAJARAN IPS SISWA KELAS VII SMP N 2 TANGEN - Rahmat Saputro, Rahmat; Sri Handayani; Daryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to design and develop an Augmented Reality (AR)-based educational game application as a learning medium for Social Studies (IPS) Geography, suitable for use by seventh-grade students at SMP N 2 Tangen. The development of this learning medium serves as an alternative to enhance students' interest and active engagement in studying Indonesian Geography material through the use of interactive and innovative technology. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The application was developed using the GDevelop 5 platform and Assemblr Edu. The feasibility test results showed that media experts achieved an average score of 80.84% (Highly Feasible), material experts achieved 81.67% (Highly Feasible), educators achieved 85% (Highly Feasible), and the student trial achieved 100% (Highly Feasible). In conclusion, the AR-based educational game application